External cephalic version - what do portuguese obstetricians think? - Cruz,Laura (2023)
Abstract Introduction: External cephalic version (ECV) is a procedure to change the presentation of the fetus from breech, transverse, or oblique to vertex by applying pressure externally to the fetus through the gravid abdomen. Aim: To evaluate the use of external cephalic version (ECV) among the portuguese obstetric community and the reasons for not performing this procedure. Study design: Cross-sectional study. Population: Doctors attending the 5th national Congress of Obstetrics and Maternal-Fetal Medicine in 2019. Methods: A cross-sectional survey using self-administered questionnaires was conducted among doctors attending the national obstetrics congress in 2019. The survey evaluated the local of work, the level of experience, motivation, and capability of performing an ECV by the participants as well as the reasons for not suggesting or performing an ECV. The statistical analysis included descriptive and comparative analysis. The chi-square test was used with a significance level < 0,05. Results: Ninety-nine clinicians answered the questionnaire; fifty-two worked in a differentiated perinatal hospital. ECV was mainly recommended by doctors from differentiated perinatal hospital (n=29) when compared to doctors from private hospitals (n=2) and perinatal hospitals (n=10) (p =0,010). Most clinicians (n=58) would not recommend this procedure to pregnant women. The main reasons for this were the lack of clinical experience (n=39) and the fact that participants believed that cesarean was a more adequate procedure (n=15). Eighty-one participants were interested in attending training sessions to learn how to perform an EVC in safe conditions. Conclusion: Overall, ECV is not widely practiced in Portugal despite being a safe procedure recommended by the Portuguese Society of Obstetrics and Maternal-Fetal Medicine. Efforts should be done to implement this safe technique among clinicians through training sessions or to enhance referral of these patients to institutions where ECV is performed.